ANALISIS KREATIVITAS IKLAN DAN PROMOSI PENJUALAN TERHADAP MINAT BELI MINUMAN DIVA PADA MASYARAKAT DI KOTA BATAM - Saragih, Ira Aprianti; Firnandi, Arlan (SCIENTIA JOURNAL, 2019)
Each product requires a marketing strategy to attract buying interest from the community as a market or consumer of the product. The study aims to see the influence of advertising and promotion of Diva beauty drink products to the buying interest of people in the city of Batam. Diva beauty drink is a brand of beauty nutrition product from Kalbe Nutritional with subsidiary PT.Sanghiang Perkasa Batam. Ad diva beauty drink that utilizes mass media communications media as media company. Advertising is one of the determinants in attracting buyers and building strong brands that constantly remind people of the quality of the Diva brand and its programs for the community. Promotion itself is an activity to convey information, communicate, convince the public of a product. Samples taken with non probability sampling technique with accidental sampling method, and data collection techniques using survey method through questionnaire. The size of the sample taken using slovin formula is 400 respondents. Data in this research is batam city society consisting of 12 districts. Data processing method using multiple linear regression method with tools SPSS (Statistical Product and Service Solution) version 20. Based on the test results, it can be seen that the ads have a positive and significant impact on people's buying interest. promotion has a positive and significant impact on people's buying interest. Advertising and promotion partially have a positive and significant influence on people's buying interest.